2011
DOI: 10.1590/s0034-737x2011000300022
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de genótipos de feijão-mungo-verde semeados no inverno na Zona da Mata de Minas Gerais

Abstract: Avaliou-se o desempenho do feijão-mungo-verde, semeado no inverno, na Zona da Mata de Minas Gerais, a 400 (Oratórios) e 720 m (Coimbra) de altitude. Dez genótipos foram semeados no final de julho, ou no início de agosto, no delineamento em blocos ao acaso, com quatro repetições. Irrigações por aspersão complementaram as chuvas. A primeira vagem amadureceu aos 73,3 (Oratórios) e aos 79,9 dias após a emergência (DAE) (Coimbra). A altura das plantas foi maior em Oratórios (62,4 cm) do que em Coimbra (37,1 cm). Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 3 publications
1
6
0
7
Order By: Relevance
“…This trial obtained similar results to Vieira et al (2011), who studied six seed lots of mung beans germination percentage and recorded answers above 90%. Caldas (2004) also observed that the germination values of eight strains of mung beans ranged from 89 to 98%, and highlighted that the standard germination test, carried out under optimal room conditions of temperature, moisture and light, can result in maximum seed germination potential in accordance with what was observed in this study.…”
Section: Resultssupporting
confidence: 79%
“…This trial obtained similar results to Vieira et al (2011), who studied six seed lots of mung beans germination percentage and recorded answers above 90%. Caldas (2004) also observed that the germination values of eight strains of mung beans ranged from 89 to 98%, and highlighted that the standard germination test, carried out under optimal room conditions of temperature, moisture and light, can result in maximum seed germination potential in accordance with what was observed in this study.…”
Section: Resultssupporting
confidence: 79%
“…Apesar da grande parcela na produção, a produtividade nestes países ainda é baixa, algo abaixo de 1000 kg. No Brasil, as baixas produtividades com a cultura não são uma realidade diferente, em situações experimentais no estado de Minas Gerais as produtividades oscilaram entre 1093 e 801 kg ha -1 [4] Dentre os fatores que podem afetar a produtividade e crescimento vegetativo desta cultura está a nutrição mineral, principalmente a utilização do nitrogênio (N), que é o macro nutriente mais importante para as plantas, sendo exigido em maiores quantidades pela cultura. O N é constituinte de vários compostos destacando-se os aminoácidos, ácidos nucleicos e a clorofila [5].…”
Section: Doses De Nitrogênio E Níveis De Irrigação Em Feijão Mungo (Vunclassified
“…In Brazil, mungbean is cultivated on a small scale, and is little studied. Nevertheless, the species has been gaining market share, especially for the production of bean sprouts (moyashi) at different times of the year, highlighting the region of Minas Gerais (Vieira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%